![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (-a)(b-c+d) = -ab + ac - ad
b) a(a+b) - b(a+b) - (b-a)b
= a2 + ab - ab - b2 - b2 + ab
= a 2 +ab - b2
![](https://rs.olm.vn/images/avt/0.png?1311)
a, = ac+bc-ad-bd
b, = a^2+ab-ab-b^2 = a^2-b^2
c, = ab-bc+ad-bd
d, = a^2-ab+ab-b^2-b^2+ab = a^2+ab
Tk mk nha
![](https://rs.olm.vn/images/avt/0.png?1311)
A= ( a - b) - ( a - b -c ) - ( 2a + c - a)
\(=a-b-a+b+a-2a-c+a\)
\(=\left(a-a+a+a-2a\right)+\left(-b+b\right)+c\)
\(=\left(2a-2a\right)+c\)
\(=c\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = (a - b ) - ( a - b - c) - ( 2b +c - a )
= a - b - a + b + c - 2b - c + a
= ( a - a + a) - (b - b + 2b) + ( c- c)
= a - 2b + 0
= a - 2b
A= (a - b) - (a - b - c) - (2b + c - a)
= a - b - a + b + c - 2b -c + a
= a - 2b
![](https://rs.olm.vn/images/avt/0.png?1311)
( a - b ) - ( a - b - c ) - ( 2b + c - a )
= a - b - a - b - c - 2b + c - a
= a - a - a - b - b - 2b - c + c
= a - 2b
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) A = (a + b) - (a - b) + (a - c) - (a + c)
A = a + b - a + b + a - c - a - c
A = 2b - 2c
A = 2 (b - c)
b) B = (a + b - c) + (a - b + c) - (b + c - a) - (a - b - c)
B = a + b - c + a - b + c - b - c + a - a + b + c
B = 2a
a) A = ( a + b ) - ( a - b ) + ( a - c ) - ( a + c )
=a+b-a+b+a-c-a-c
=(a-a)+b+b+(-c)+(-c)
=0+2b+(-2)c
=-2(c-b)
b) B = (a+b - c ) + ( a - b + c ) -( b +c - a ) - ( a - b - c )
=a+b-c+a-b+c+b-c+a-a+b+c
=(a-a)+2(b-b)+2(c-c)+a+a+b+b
=0+0+0+2a+2b
=2(b+a)
\(a,\left(b-c\right)+\left(a-b\right)=b-c+a-b=a-c\)
\(b,\left(a+b\right)-\left(c+a\right)=a+b-c-a=b-c\)
~ ủng hộ nha ~
a/ (b-c)+(a-b)=b-c+a-b=a+c
b/(a+b)-(c-a)=a+b-c-a=b-c